2018
DOI: 10.1002/acr.23492
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perception of Disease‐Related Symptoms and Complications in Relapsing Polychondritis

Abstract: Patient-reported data in RP highlight a significant burden of disease. Patterns of organ involvement may lead to diagnostic delay and influence treatment decisions, ultimately impacting the development of disease-related complications. Timely diagnosis, standardization of treatment approaches, and prevention of disease-related complications are major unmet needs in RP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
43
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 21 publications
0
43
2
Order By: Relevance
“…For educational purposes, it should be noted that this percentage refers to the symptoms present prior to diagnosis . Ear chondritis is obviously a major clue to diagnose RP, but it frequently occurs after some delay, and therefore the reported initial symptoms are in part cumulative, as attested by the high (374%) sum of percentages . With regard to the very first manifestation(s) of RP, ear chondritis accounted for only 41% in our recent study, although the sum of percentages (in case there were several associated initial manifestations) was 176% .…”
mentioning
confidence: 56%
See 4 more Smart Citations
“…For educational purposes, it should be noted that this percentage refers to the symptoms present prior to diagnosis . Ear chondritis is obviously a major clue to diagnose RP, but it frequently occurs after some delay, and therefore the reported initial symptoms are in part cumulative, as attested by the high (374%) sum of percentages . With regard to the very first manifestation(s) of RP, ear chondritis accounted for only 41% in our recent study, although the sum of percentages (in case there were several associated initial manifestations) was 176% .…”
mentioning
confidence: 56%
“…Very recently, Shimizu et al reported that airway involvement was associated positively with nasal chondritis and negatively with external ear chondritis, but we had difficulties confirming this report . Similar studies would be difficult to draw from the article by Ferrada et al, partly because acquired nasal deformity, which can occur without any prior pain or inflammation, was not included in the survey .…”
mentioning
confidence: 62%
See 3 more Smart Citations